Dupuytren's disease - Rames Mattar Junior (Einstein (São Paulo), 2008)
Dupuytren’s disease is one of the most frequent conditions seenby practicing hand surgeons. Inherited in an autosomal dominantpattern, the disease is characterized by a nodular thickening of thepalmar fascia metacarpophalangeal and proximal interphalangealjoints. It is more frequent in young men than in women, but in old ageits frequency may equal in men and women. Treatment is offered tosymptomatic patients with painful nodular or disabling contracture.The most prevalent surgical procedure is limited fasciectomy of theinvolved abnormal structures and recurrence is common.